#We are not Charlie: Muslims' differentiated reactions to the Paris Attacks, and the dangers of indiscriminate finger-pointing - Jannis Grimm (Stiftung Wissenschaft und Politik (SWP), 2015)
After the January 2015 attacks in Paris, Muslims from all over the world showed impressive solidarity with the victims. This was the more surprising given that the victims included cartoonists working for the satirical magazine "Charlie Hebdo", whose caricatures of Mohammed had previously caused mass protests in predominantly Muslim states. However, European media took more notice of the protests against the new edition of the satirical magazine than of the declarations of solidarity. This selective perception can partly be explained by the fact that European societies constantly expect Muslims to distance themselves from violent acts committed in the name of Islam. These demands reinforce negative associations of Islam with terrorism and violence, and nourish threat perceptions and anti-Islamic prejudices, which in turn contribute to Muslims feeling increasingly excluded in Europe. Extremists can take advantage of this alienation for recruiting purposes. To counter this danger, politicians and the media must act decisively against negative portrayals of Islam and reduce the pressure put on Muslims to justify themselves, a pressure that deepens the division of European societies. (SWP Comments)
Keywords: 300